International macroeconomics - Montiel, Peter J. 1951- (Wiley-Blackwell, 2009)
Utilizing a unified, single-model approach, this textbook guides the reader through a broad range of policy issues, historic cases, institutions, and specific countries, which allows for an extensive overview of macroeconomics within an international context.